Evaluation of Gas 6 as a Prognostic Marker in Papillary Renal Cell Carcinoma - Mikuteit, Marie; Zschäbitz, Stefanie; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Urologia Internationalis, 2023)
Introduction: Growth arrest-specific protein 6 (Gas 6) is a ligand that plays a role in proliferation and migration of cells. For several tumor entities, high levels of Gas 6 are associated with poorer survival. We examined the prognostic role of Gas 6 in renal cell carcinoma (RCC), especially in papillary RCC (pRCC), which is still unclear. Methods: The patients' sample collection is a joint collaboration of the PANZAR consortium. Patients' medical history and tumor specimens were collected from n = 240 and n = 128 patients with type 1 and 2 pRCC, respectively. Expression of Gas 6 was determined by immunohistochemistry. Results: In total, Gas 6 staining was evaluable in 180 of 240 type 1 and 110 of 128 type 2 pRCC cases. Kaplan-Meier analysis disclosed no significant difference in 5-year overall survival for all pRCC nor either subtype. Also, Gas+ and Gas- groups did not significantly differ in any tumor or patient characteristics. Conclusion: Gas 6 was not found to be an independent prognostic marker in pRCC. Future studies are warranted to determine if Gas 6 plays a role as prognostic marker or therapeutic target in pRCC.
CRIS-Team Scopus Importer:2023-08-11